Pain reduction methods during transurethral cystoscopy - Łaszkiewicz, Jan; Krajewski, Wojciech; Łuczak, Mateusz; Chorbińska, Joanna; Nowak, Łukasz; Bardowska, Klaudia; Zdrojowy, Romuald (Contemporary Oncology/Współczesna Onkologia, 2021)
Transurethral cystoscopy (CS) is a common urological procedure, performed mostly for diagnostic but also for therapeutic purposes. Although CS is generally well tolerated, some patients describe the pain related to the procedure as high or even “unbearable”. As a result, many patients fear and avoid both primary and/or follow-up cystoscopies. This may lead to uncontrolled progression of neoplastic disease. Therefore, it is crucial to maximally increase the comfort of the patient and to implement safe and effective analgesia before the procedure. Providing the patients with appropriate care during CS can encourage them to comply with diagnostic schedules and improve their prognosis. The aim of this review is to analyze the available literature on various methods of pain reduction during transurethral CS. The PubMed electronic database limited to English articles published until January 2021 was used in the process. Meta-analyses, systematic reviews, randomized controlled trials, clinical trials, prospective randomized studies, multicenter comparisons, reviews and retrospective comparisons were used. As a result, 65 articles were included in this review.